The Preparation of Gen-NH2-MCM-41@SA Nanoparticles and Their Anti-Rotavirus Effects - Lijun Song; Jiabo Chen; Yuxuan Feng; Yujing Zhou; Feng Li; Guiqin Dai; Yue Yuan; Haosen Yi; Yupei Qian; Siyan Yang; Yang Chen; Wenchang Zhao (MDPI AG, 2022)
Genistein (Gen), a kind of natural isoflavone drug monomer with poor water solubility and low oral absorption, was incorporated into oral nanoparticles with a new mesoporous carrier material, NH2-MCM-41, which was synthesized by copolycondensation. When the ratio of Gen to NH2-MCM-41 was 1:0.5, the maximum adsorption capacity of Gen was 13.15%, the maximum drug loading was 12.65%, and the particle size of the whole core-shell structure was in the range of 370 nm-390 nm. The particles were characterized by a Malvern particle size scanning machine, XRD, Fourier transform infrared spectroscopy, scanning electron microscopy, and nitrogen adsorption and desorption. Finally, Gen-NH2-MCM-41 was encapsulated by sodium alginate (SA), and the chimerism of this material, denoted as GEN-NH2-MCM-41@SA, was investigated. In vitro release experiments showed that, after 5 h in artificial colon fluid (pH = 8.0), the cumulative release reached 99.56%. In addition, its anti-rotavirus (RV) effect showed that the maximum inhibition rate was 62.24% at a concentration of 30 μM in RV-infected Caco-2 cells, and it significantly reduced the diarrhea rate and diarrhea index in an RV-infected-neonatal mice model at a dose of 0.3 mg/g, which was better than the results of Gen. Ultimately, Gen-NH2-MCM-41@SA was successfully prepared, which solves the problems of low solubility and poor absorption and provides an experimental basis for the application of Gen in the clinical treatment of RV infection.